Application of Measuring Instruments with Elements of Artificial Intelligence to Optimize Cross-Cultural Communications of Personnel of Outsourcing Sewing Enterprises. - Rogozhina, Iulia; Guseva, Marina; Andreeva, Elena (SHS Web of Conferences, 2023)
Continuous changes in the global world affect the interaction of Russian and foreign enterprises. The long-term experience of cooperation between the sewing enterprises of Russia and China has shown that for the fruitful development of relations in a period of unstable international situation, it is necessary to introduce a new communication format into the production cycle digital quality control of semi-finished and finished clothing products. Since the middle of the last century, outsourcing has become an actual form of development of the global clothing industry, involving remote interaction between the head offices of design firms and contractor factories. A feature of labor relations at outsourcing enterprises is the maintenance of norms and values of business cultures of cooperating countries. Due to interethnic differences in the interpretation of such a basic concept in the industry as "the quality of sewing", controversial situations often arise that reduce the positive image and reputation of representatives of conflicting parties. The introduction of a contactless form of acceptance of finished products using the computer vision tool will not only optimize the final inspection stage, but also improve the psychological climate when interacting with the controller-inspector and employees of the outsourcing factory. Computer vision effectively detects the emerging defect among semi-finished garments.